Glass sand potentiality of bar sediments from Tista and Dharla rivers, Bangladesh (Rajshahi University Journal of Life & Earth and Agricultural Sciences, 2015)
The present investigation deals with the glass sand potentiality of the barsediments of Tista and Dharla rivers from different locations of Nilfamari,Lalmonirhat and Kurigram districts, Bangladesh. Accordingly, fourteen sampleswere selected for grain size distributions with separation of magnetic minerals.Magnetic mineral content ranges from about trace amount to 0.06 wt%. Lightminerals separated by tetrabromoethane technique ranging from about 88 to 98 wt%. Moreover, glass sand as final products by flotation process evaluationranges from 58 to 80 wt%, which indicate good quantity of glass sand.Geochemical data also suggest that glass sands are suitable for commercial grade glass owing to its SiO2 content (80.794.1 wt%). In particular, the Tista Barrage site shows high SiO2 (94.1 wt%) with reasonably low Al2O3, TiO2, andMgO+CaO percentages, which suggest an excellent glass grade quality.Unfortunately, some impurities (e.g., Fe2O3, Zr) are comparatively higher thanstandards, which poses difficulties making high grade glass. However, if it ispossible to remove and/or decrease the major impurities, it may be used tomanufacture high grade glass (colourless glass).